2004
DOI: 10.1164/rccm.200309-1305oc
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-four–hour Ambulatory Blood Pressure in Children with Sleep-disordered Breathing

Abstract: Obstructive sleep apnea causes intermittent elevation of systemic blood pressure (BP) during sleep. To determine whether obstructive apnea in children has a tonic effect on diurnal BP, 24-hour ambulatory blood pressure was obtained from 60 children with mean age of 10.8 Ϯ 3.5 years. Thirty-nine children had obstructive apnea and 21 had primary snoring. Children with obstructive apnea had significantly greater mean BP variability during wakefulness and sleep, a higher night-to-day systolic BP, and a smaller noc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
219
2
20

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(248 citation statements)
references
References 54 publications
7
219
2
20
Order By: Relevance
“…Ambulatory 24-hour BP recordings on 39 children with OSA and 21 with simple snoring showed increased BP variability during wakefulness and sleep and less nocturnal BP dipping in children with OSA compared with children with simple snoring. 382 In addition to BMI, the frequency of oxygen desaturation during sleep and AHI were significant predictors for daytime and nocturnal BP variability, respectively. However, compared with snoring children, those with OSA did not have higher daytime or nighttime BP.…”
Section: Hypertensionmentioning
confidence: 90%
“…Ambulatory 24-hour BP recordings on 39 children with OSA and 21 with simple snoring showed increased BP variability during wakefulness and sleep and less nocturnal BP dipping in children with OSA compared with children with simple snoring. 382 In addition to BMI, the frequency of oxygen desaturation during sleep and AHI were significant predictors for daytime and nocturnal BP variability, respectively. However, compared with snoring children, those with OSA did not have higher daytime or nighttime BP.…”
Section: Hypertensionmentioning
confidence: 90%
“…These parameters include increases in both BP surge and BP load, as well as the previously described changes in BP variability and nocturnal BP dipping. 7 …”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that in a group of children with SDB, the severity of the disorder was associated with increased BP variability and decreased nocturnal dipping. 7 Additionally, several cross-sectional studies have described trends of increasing BP with greater frequency of apnea and hypopneas index (AHI) during sleep. 8 -10 To date, however, the level of SDB severity at which BP in pediatric SDB patients begins to diverge from that of healthy controls is not known.…”
mentioning
confidence: 99%
“…Immediate consequences of OSAS are sleep fragmentation, arousal, poor school/job performance, irritability, intermittent hypercapnia and hypoxemia, nocturnal hypertension and marked changes in autonomic control of the cardiovascular system. 88 The long-term consequences of OSAS include sustained daytime and nocturnal hypertension, 89,90 cor pulmonale, left ventricular hypertrophy 91 and increased cardiovascular and cerebrovascular morbidity and mortality. 92 Indeed, cross-sectional results from the Sleep Heart Health Study showed a strong association between OSAS, heart failure and stroke.…”
Section: Cardiovascular Risksmentioning
confidence: 99%